Comparative Study of Drinking Water of Three Different Schools of Damak, Jhapa - Shrestha, Arun Kumar; Rustagi, Josika; Khatiwada, Asmita; Bhandari, Nabin; Budhathoki, Himalaya; Niraula, Swastika; Shrestha, Ganesh Kumar; Shah, Buddha Ram; Koirala, Ram Prasad (Damak Campus Journal, 2023)
The health and well-being of society are measured by the quality of the water. Thus, it is the most important issues facing the entire planet today. The main aim of the work is to evaluate the WQI of three different school to check the quality of drinking water. The WQI value for Singha Devi Secondary, Oxford English and Himjyoti English are 45.36, 36.73 and 64.69 respectively. The water of Singha Devi and Oxford falls in good category whereas water of Himjyoti falls in poor category.Which shows that groundwater of Himjyoti is relatively contaminated. All these three waters are suitable for drinking, but certain treatment is required to retain their quality.